Tuberculosis presenting as immune thrombocytopenic purpura - Bahadir-Erdogan Beril; Kunt-Uzaslan Esra; Ozkocaman Vildan; Ozcelik Tulay; Ozkan Atilla; Ali Ridvan; Ozkalemkas Fahir; Akalin Halis (Annals of Clinical Microbiology and Antimicrobials, 2004)
Abstract Background Although various hematologic abnormalities are seen in tuberculosis, immune thrombocytopenic purpura is a rare event. Case Presentation We report a case of a 29 year-old male who was presented with immune thrombocytopenia-induced hemoptysis, macroscopic hematuria and generalized petechiae. The patient was found to have clinical, microbiological and radiological evidence of active pulmonary tuberculosis. The immune thrombocytopenic purpura was successfully treated with anti-tuberculous drugs combined with corticosteroids and high dose immune globulin therapy. Conclusion Immune thrombocytopenic purpura can be one of the hematological manifestations of tuberculosis which has a global prevalence with increasing incidence secondary to HIV infection.